Perancangan Dan Implementasi Sistem Informasi Inventaris Barang Desa Batu Raja Lampung Utara - Erwanda; M. Abu Jihad Plaza R (Riset Sinergi Indonesia (RISINDO), 2026)
This study aims to design and implement a web-based inventory information system to address asset management issues at the Batu Raja Village Office, North Lampung. Currently, inventory management is still carried out conventionally, resulting in data irregularities, a high risk of input errors, and inefficiencies in the reporting process. To address these challenges, this study utilized data collection techniques through observation, interviews, and literature studies. Software development was carried out using the Waterfall method sequentially, starting from needs analysis to system implementation. The result of this study is a web-based inventory information system capable of centrally integrating village asset data. The implementation of this system is expected to improve the accuracy of asset data collection, accelerate reporting workflows, and provide support for village officials in making strategic decisions related to more accountable and transparent village asset management